COMPARISON OF AGILE VS WATERFALL VS DEVOPS METHODOLOGIES IN SOFTWARE PROJECT SUCCESS - Calvina Suhas Maharao, Dr. Archana Tukaram Bhise (International Journal of Research Science and Management, 2023)
The software development industry is constantly evolving, with organizations continually seeking to optimize their project delivery processes. Agile, Waterfall, and DevOps are three distinct methodologies that have been extensively used to manage and execute software development projects. This research paper aims to compare these three methodologies in the context of software project success. By examining their characteristics, advantages, challenges, and their overall impact on software project outcomes, this paper provides insights into which methodology may be best suited for different types of software projects. The paper further discusses the integration of DevOps into Agile and Waterfall approaches, the trends influencing these methodologies, and the overall impact on project management.